Technical Publication for Vehicle Users in Support of Environmental Pollution Reducing - Hajderi, Asllan; Vyshka, Eli (Mediterranean Journal of Social Sciences, 2012)
In this study, it is addressed the problem of reducing pollution through the use of technical publications for vehicle users.They will inform the user in terms of vehicle choice with the lesser degree of pollution and recognition of ways for reducing of thepollution level for vehicles in use. Also provision of knowledge on damage that vehicle gases cause on human health will lead toincreased interest in knowing the ways and new technologies in terms of reducing pollution from vehicles, which they use. Below it isshown the analysis of pollutant emissions that vehicles generate in the atmosphere, depending on years of production according tomanufacturing factory, for the years 1992-2009. While it is shown the current situation of the structure of vehicles in Albania, from whichresults, that dominate vehicles manufactured before 1996 at over 70%. From the study it results, that if the vehicles in circulation will beonly produced vehicles after 2000-2005, the pollution level reduction in urban centers will be reduced at least 3 times. At the bottom it isanalyzing the impact of technical maintenance of vehicles, to their pollution level. Results show that a bad technical maintenance of thevehicle during use, could lead to the growth of polluting emissions by 3 times compared to standards. For this the methods used todayto maintain engine performance and emission reduction of vehicles in use are shown. Subsequently it is shown that providing technicalmaintenance of vehicles in circulation will become through technical publications and environmental additional tax and therefore we willachieve a reduction of the pollution level in urban areas over 2 times.